TEOLOGI TAUHID TRANSFORMATIF DAN KONSELING INTEGRATIF-HOLISTIK SEBAGAI PARADIGMA MASYARAKAT NON-KEKERASAN - Indira Rahma Ayu Nashiroh; Mira Dwi Adhelia; Kaesa Yumna Salsabila; Moh. Ali Imron; Ali Hasan Siswanto (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The reality of violence in contemporary society is undergoing increasingly complex transformations, taking the form not only of physical violence but also of structural, symbolic, digital, and religiously based violence. This phenomenon points to a spiritual crisis, social disintegration, and a weak foundation of ethical consciousness in modern life. Previous studies on non-violent societies have tended to be dominated by sociological, political, and legal approaches that have not sufficiently integrated theological, psychological, and spiritual dimensions as the basis for social transformation. On the other hand, studies on Islamic counseling generally remain oriented toward individual-therapeutic approaches and have not yet been developed as a paradigm for the reconstruction of a peaceful society. Addressing this gap, this study aims to construct the “Transformative Tawhid Theology” paradigm through the Integrative-Holistic Tawhid Counseling Approach as a model for creating a non-violent society. This study employs a qualitative method with a philosophical-critical approach and integrative conceptual analysis of literature in Islamic theology, Sufism, spiritual psychology, and peace studies. This study argues that Tawhid functions not only as a normative doctrine but also as a transformative consciousness capable of shaping emotional regulation, social empathy, collective resilience, and a culture of peace. The integration of spiritual, psychological, and social dimensions in Tawhid counseling yields a model of social healing focused on the transformation of consciousness and the reconstruction of human relationships. The scientific contribution of this research lies in the formulation of a new interdisciplinary paradigm that links theology, Sufism, Islamic counseling, and social transformation as the epistemological foundation of a nonviolent society based on the value of rahmatan lil ‘alamin.